Impact of Television Serials on Women’s Empowerment: A Study Among Women in Chennai - V, Elizabeth Mary (Journal of Advanced Research in Journalism & Mass Communication, 2023)
This research study focuses on television serials impact on women’s empowerment in decision making and the portrayal of women in reel and real life. This research was based on the quantitative method and the data in this study was taken through random sampling method with the use of google form. The sampling size for this study was 103 women under the age category of 25years to above 50years respondents from Chennai. The researcher adapted the Mahmud et al. conceptual frameworks that view women’s empowerment as a multi-faceted and dynamic process. In this research paper, the researcher has stated various definitions of empowerment, including the ability to stand on their own feet, the capacity to grow stronger and more self-assured, the television serials undoubtedly have a big impact on people and could be a very effective tool for promoting gender equality and raising the status of women in today’s society. The majority of women place a strong emphasis on overcoming their hardships and becoming strong, independent women. And there is huge difference in decision making while comparing real and reel life of women and the way of portraying women in television. How to cite this article: Mary VE. Impact of Television Serials on Women’s Empowerment: A Study Among Women in Chennai. J Adv Res Jrnl Mass Comm 2023; 10(2): 22-25 DOI: https://doi.org/10.24321/2395.3810.2023011